BOOK REVIEWS. Issue 3 (1st September 2013) - Chrystall, Andrew; Johnson-Woods, Toni; Laugesen, Amanda; Laugesen, Amanda; Franks, Rachel; Braae, Nick; Foley, Dennis; Russell, Keith
ANNA MAY WONG'S LUCKY SHOES: 1939 AUSTRALIA THROUGH THE EYES OF AN ART DECO DIVA, DERHAM GROVES (2011) Ames, IA: Culicidae Press, 103 pp., ISBN: 978-1-257-71315-8, p/bk, AUS39.95WHACKADEMIA: AN INSIDER'S ACCOUNT OF THE TROUBLED UNIVERSITY, RICHARD HIL (2012) Sydney: New South Press Press, ISBN: 9781742232911; 240 pp., p/bk, RRP AUD34.99CAMOUFLAGE AUSTRALIA: ART, NATURE, SCIENCE AND WAR, ANN ELIAS(2011) Sydney: Sydney University Press, 239 pp., ISBN: 9781920899738, p/bk, AUD60.00WITNESSES TO WAR: THE HISTORY OF AUSTRALIAN CONFLICT REPORTING, FAY ANDERSON AND RICHARD TREMBATH (2011) Melbourne: Melbourne University Press, 500 pp., ISBN: 2780522856446, p/bk, AUS36.99, ISBN: 9780522860221, e-publication.ENDING WAR, BUILDING PEACE, LYNDA-ANN BLANCHARD AND LEAH CHAN (EDS) (2009) Sydney: Sydney University Press, 187 pp., ISBN: 781920899431, p/bk, AUS35.00SPHERE OF INFLUENCE: WRITINGS ON CRICKET AND ITS DISCONTENTS, GIDEON HAIGH (2010) Melbourne: Victory Books, 386 pp., ISBN: 978-0-522-85787-0, p/bk, AUD 34.99RE-AWAKENING LANGUAGES: THEORY AND PRACTICE IN THE REVITALISATION OF AUSTRALIA'S INDIGENOUS LANGUAGES, JOHN HOBSON, KEVIN LOWE, SUSAN POETSCH AND MICHAEL WALSH (EDS) 2010 Sydney: Sydney University Press, 457 pp., ISBN: 9781920899554, p/bk, AUS65.00.GLOBAL TECHNOLOGICAL CHANGE: FROM HARD TECHNOLOGY TO SOFT TECHNOLOGY, ZHOUYING JIN (2011) 2nd ed., Bristol, UK: Intellect, 366 pp., ISBN: 978-1-84150-376-9, p/bk, AUS69.95